Technical and economic aspects of industrial laundry wastewater treatment = Techniczne i ekonomiczne aspekty oczyszczania ścieków pralniczych - Bering, Sławomira; Mazur, Jacek; Tarnowski, Krzysztof (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Three biological methods of laundry wastewater purification were tested, in pilot scale, in Fliegel Textilservice laundry in Nowe Czarnowo. Among tested methods, rotating biological contactor, membrane bioreactor and sponge activated sludge reactor, the last one has been pointed out as optimal for laundry wastewater treatment.
Keywords: pralnia; ścieki pralnicze; biologiczne oczyszczanie ścieków; laundry; wastewater; membrane biological reactor; rotating biological contactor; sponge activated sludge reactor